2005
DOI: 10.1111/j.1440-172x.2005.00517.x
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the relationship between nursing protocols and nursing practice in an Irish intensive care unit

Abstract: Nursing practice no longer relies on tradition or ritual; instead, it is based on research and empirical evidence. The emphasis on evidence-based nursing, as well as standardization of nursing practice, has resulted in the production of policies, protocols and guidelines aimed at directing numerous aspects of nursing care. The aim of this study was to explore the relationship between these documents and actual nursing practice. To this end, this descriptive study employed a case study approach to examine the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
25
1
1

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(27 citation statements)
references
References 20 publications
0
25
1
1
Order By: Relevance
“…2004a, Blackwood & Wilson‐Barnett 2007). In contrast, a study exploring the perceptions of intensive care nurses to policies, protocols and guidelines found that there was a fear that protocols were ‘taking the thinking out of nursing’ and deprived inexperienced nurses of an opportunity to develop decision‐making skills (Flynn & Sinclair 2005).…”
Section: Introductionmentioning
confidence: 99%
“…2004a, Blackwood & Wilson‐Barnett 2007). In contrast, a study exploring the perceptions of intensive care nurses to policies, protocols and guidelines found that there was a fear that protocols were ‘taking the thinking out of nursing’ and deprived inexperienced nurses of an opportunity to develop decision‐making skills (Flynn & Sinclair 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Thus it has been argued that the evidence base of guidelines has been rather narrow and too medically oriented, and to the neglect of other kinds of knowledge important to nursing practice (Swinkels et al 2002; Geanellos 2004). It is also argued that guidelines oversimplify patient care by forgetting the uniqueness of each patient's situation; and, finally, it is also said to threaten the clinical autonomy of nurses (Bradshaw 2000; Flynn & Sinclair 2005; Taylor & Allen 2007).…”
Section: Introductionmentioning
confidence: 99%
“…More than 20% of respondents in a recent survey of more than 1300 predominantly nursing clinicians agreed that practice "guidelines are too cookbook and prescriptive" [25]. Another study also found that nurses were afraid that protocols "were taking the thinking out of nursing" [26]. Within the current survey, greater than 25% of respondents also indicated that protocols cause confusion among clinicians.…”
Section: Discussionmentioning
confidence: 79%